(untitled) (Kinesiology, 2023)
The purpose was to ascertain the effects of a 12-week intervention program based on exercises of mobility and dynamic strength on the stabilization of neck and trunk muscles in people with neck or low back pain according to gender. Forty-two subjects (n = 25 males and n = 17 females; age 49.62±8.82 years) with neck or low back pain completed a recovery-training program focused on improving mobility and strength in the stabilizing muscles of the trunk and neck. A range of motion test, a strength (maximum voluntary contraction) test and the muscle strength asymmetry of the muscle groups analyzed were assessed at the beginning (T1), after six (T2) and after 12 (T3) weeks of intervention. Improvements were seen in nine out of the 12 range of motion variables at T2 (ES=0.52 to 1.26, moderate-high; p<.05) and T3 (ES=-0.28 to -0.44, low; p<.05 or p<.01). Improvements were also evident in all the strength variables at T2 (ES=-0.81, high; p<.01) and T3 (ES=-1.08 to -0.95, high; p<.01). In contrast, in the strength asymmetry variables improvements were found in one out of the five variables analyzed at T2 (ES=-0.81, high; p<.01) and two out of five at T3 (ES=- 1.08 to -0.95, high; p<.01). In conclusion, the intervention was effective for improving range of motion and strength. However, to improve muscle strength asymmetry it may be necessary to include specific exercises. Key words: mobility, force, training, pathology, spine